Climate for Innovation impacts on Adaptive Performance. Conceptualization, Measurement, and Validation = Wpływ klimatu sprzyjającego innowacjom na adaptacyjność indywidualną. Konceptualizacja, pomiar i walidacja - Stańczyk, Sylwia (Zielona Góra: Faculty of Economics and Management Press)
The main objective of this paper was to examine the relationship between organizational climate for innovation and adaptive performance. The study was carried out in business organisations in Poland (N=387), representing variety of industries. The Cimate for Innovation measure and Individual Adaptive Performance measure was adopted from previous studies.
Keywords: innowacyjność; sprzyjające warunki; adaptacyjność indywidualna; walidacja; narzędzia badawcze; innovation; climate for innovation; adaptive performance; instrument validation